Transient visual loss with methotrexate, leucovorin chemotherapy for gestational trophoblastic neoplasia: Happenstance or beyond? (Indian Journal of Case Reports, 2018)
Methotrexate chemotherapy (CT) is a standard for low-risk gestational trophoblastic neoplasia. Its use is associated with minimal toxicities and is chiefly composed of mild nausea and vomiting. Acutely occurring and self-limiting loss of vision has not been reported in the literature as a potential side effect. We discuss such a case with a transient and self-limiting visual loss in a patient on two consecutive courses of the planned CT. We advocate a further in-depth research to find the cause of such an association.